Poor early graft function impairs long-term outcome in living donor kidney transplantation - Hellegering, J. (Springer Berlin Heidelberg, 2012)
BACKGROUND: Poor early graft function (EGF) after living donor kidney transplantation (LDKT) has been found to decrease rejection-free graft survival rates. However, its influence on long-term graft survival remains inconclusive. METHODS: Data were collected on 472 adult LDKTs performed between July 1996 and February 2010. Poor EGF was defined as the occurrence of delayed or slow graft function. Slow function was defined as serum creatinine above 3.0 mg/dL at postoperative day 5 without dialysis. RESULTS: The incidence of slow and delayed graft function was 9.3 and 4.4%, respectively. Recipient overweight, pretransplant dialysis and warm ischemia were identified as risk factors for the occurrence of poor EGF. The rejection-free survival was worse for poor EGF as compared to immediate graft function with an adjusted hazard ratio (HR) of 6.189 (95% CI 4.075–9.399; p < 0.001). Long-term graft survival was impaired in the poor EGF group with an adjusted HR of 4.206 (95% CI 1.839–9.621; p = 0.001). CONCLUSIONS: Poor EGF occurs in 13.7% of living donor kidney allograft recipients. Both, rejection-free and long-term graft survivals are significantly lower in patients with poor EGF as compared to patients with immediate graft function. These results underline the clinical relevance of poor EGF as phenomenon after LDKT.